2006
DOI: 10.1038/sj.tpj.6500400
|View full text |Cite
|
Sign up to set email alerts
|

PP2A-Bγ subunit and KCNQ2 K+ channels in bipolar disorder

Abstract: Many bipolar affective disorder (BD) susceptibility loci have been identified but the molecular mechanisms responsible for the disease remain to be elucidated. In the locus 4p16, several candidate genes were identified but none of them was definitively shown to be associated with BD. In this region, the PPP2R2C gene encodes the Bg-regulatory subunit of the protein phosphatase 2A (PP2A-Bg). First, we identified, in two different populations, single nucleotide polymorphisms and risk haplotypes for this gene that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 52 publications
2
59
0
Order By: Relevance
“…35 However, there was no significant association between the cis SNPs and the expression level of the gene in the SNPExpress database, 24 and we were unable to confirm the SNP association in our samples, as the gene is absent from our expression microarray data set. Nevertheless, deficits in oligodendrocytes have been identified as a significant neuropathology in schizophrenia and in bipolar disorder, 36,37 and genome-wide expression profiling revealed that oligodendrocyte-related genes are downregulated in the PFC of both schizophrenia and bipolar disorder.…”
Section: Discussionmentioning
confidence: 67%
“…35 However, there was no significant association between the cis SNPs and the expression level of the gene in the SNPExpress database, 24 and we were unable to confirm the SNP association in our samples, as the gene is absent from our expression microarray data set. Nevertheless, deficits in oligodendrocytes have been identified as a significant neuropathology in schizophrenia and in bipolar disorder, 36,37 and genome-wide expression profiling revealed that oligodendrocyte-related genes are downregulated in the PFC of both schizophrenia and bipolar disorder.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, the M-type potassium channel subunit gene, Kcnq2, has been identified as a putative GSK3␤ substrate (Borsotto et al, 2007). Loss-of function mutations in Kcnq2 result in a mild form of epilepsy Singh et al, 1998;Cooper et al, 2000;Mulley et al, 2003) and a mutation in the phosphatidylinositol 4-phosphate 5-kinase II␣ (PIP5K2A) gene, which leads to reduced M-channel activity, has been linked to schizophrenia (Fedorenko et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several cases have been reported with typical epileptic manifestations of R(20) syndrome without KCNQ2 deletion, probably due to a dysregulation of its expression or telomeric instability leading to interstitial deletion 2122 or PPP2R2C 23…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, ezogabine has been removed from prescription after a warning from the Food and Drug Administration due to retinal pigmentary changes and blue skin discoloration with chronic use 28. Interestingly, ezogabine and lithium share similar final pathways and could both trigger the opening of potassium voltage‐gated channels 23, 27. By maintaining the KCNQ2 channel open, they may reduce the excitability of the postsynaptic neuron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation